2020
DOI: 10.1093/sleep/zsaa106
|View full text |Cite
|
Sign up to set email alerts
|

Estimating daytime sleepiness with previous night electroencephalography, electrooculography, and electromyography spectrograms in patients with suspected sleep apnea using a convolutional neural network

Abstract: A common symptom of obstructive sleep apnea (OSA) is excessive daytime sleepiness (EDS). The gold standard test for EDS is the multiple sleep latency test (MSLT). However, due to its high cost, MSLT is not routinely conducted for OSA patients and EDS is instead evaluated using sleep questionnaires. This is problematic however, since sleep questionnaires are subjective and correlate poorly with the MSLT. Therefore, new objective tools are needed for reliable evaluation of EDS. The aim of this study was to test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Some researchers modified convolutional neural networks models, which are originally used for 2D classification tasks to do 1D signal classification. On the other hand, time-frequency spectrum representations like wavelet based scalograms [12][13][14] and Short Time Fourier transform based spectrograms [15][16][17][18][19] provide multidimensional analysis of biological signals and they are generated to form 2D images to feed the network. In the literature, many studies focus on ECG signals which are found to be significantly associated with respiratory events.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers modified convolutional neural networks models, which are originally used for 2D classification tasks to do 1D signal classification. On the other hand, time-frequency spectrum representations like wavelet based scalograms [12][13][14] and Short Time Fourier transform based spectrograms [15][16][17][18][19] provide multidimensional analysis of biological signals and they are generated to form 2D images to feed the network. In the literature, many studies focus on ECG signals which are found to be significantly associated with respiratory events.…”
Section: Introductionmentioning
confidence: 99%
“…Layering automated analysis of physiologic responses on top of existing automation of traditional scoring will allow for a deeper understanding of patient-level data and the identification of additional features that contribute to meaningful disease outcomes in future research. For example, neural networks can meaningfully predict patient-relevant outcomes, such as daytime sleepiness [ 56 ]. Going beyond OSA itself, the data contained within a PSG and processed via neural networks can predict mortality, with much of the risk attributable to sleep fragmentation [ 57 ].…”
Section: Applying Machine Learning and Artificial Intelligence To Obs...mentioning
confidence: 99%
“…As sleep recordings are now digitised, there is no need to be restricted by practical constraints as it was in the 1970s when sleep recordings were paper based. To overcome these limitations, we have already started to develop ML-based methods to analyse sleep studies and estimate the severity of OSA and related daytime symptoms (Huttunen et al, 2021;Korkalainen et al, 2019;Nikkonen et al, 2019Nikkonen et al, , 2020Nikkonen et al, , 2021. Moreover, we will continue this work and produce fully-automated deep-learning-based analysis algorithms for PSGs and HSATs using state-of-the-art methods such as convolutional neural networks and recurrent neural networks.…”
Section: The Objectives Of the Sleep Revolutionmentioning
confidence: 99%